THE EFFECT OF VISA EXEMPTION POLICY ON INDONESIAN EXPORT - Banga Malewa; Muhhamad Halley Yudhistira (Universitas Udayana, 2024)
This study examines the effect of the visa exemption policy on Indonesia’s exports, by using Staggered Difference in Difference (DID) method and Indonesia's export data to 191 partner countries in 2015 - 2019 period. This study finds that visa exemption policy of Indonesia has effect on its export, but it is not